A study of submarine steep slope failures triggered by thermal dissociation of methane hydrates using a coupled CFD-DEM approach - Jiang, M; Sun, C; CROSTA, GIOVANNI; Zhang, W. (Engineering Geology, 2015)
This paper presents an extended numerical study on submarine landsliding induced by instantaneous thermal dissociation of a methane hydrate layer, by considering different dissociation scenarios in terms of position and volume of dissociated gas hydrates. A novel scheme of coupling computational fluid dynamics and distinct element method (CFD-DEM) is implemented. The behavior of fluid is simulated by CFD incorporating an empirical equation of state for slightly compressible liquid, whereas that of sediment skeleton with methane hydrates by DEM through a two-dimensional thermo-hydro-mechanical bond contact model. The scenario of whole hydrate dissociation identifies four typical stages of submarine landsliding: the initiation of landslide after hydrate dissociation, the onset of the submarine landslide, the sliding process, and the final deposition and stabilization, which is characterized by some microscopic variables (e.g. particle displacement, fluid velocity, excess hydrostatic pressure, particle-scale energy input and dissipation) so to attain a complete analysis of the landslide process. Reasonable representation of the slope instability phenomenon as triggered by thermal dissociation of gas hydrates is obtained. Besides, slope failure scenarios with different positions and volumes of the occurring MH dissociation are presented to better understand their influence on the evolution of the instability. Four landslide types are generated by the different dissociation scenarios: fall, slump, flow and a combination of slump and flow, which are further analyzed by outputting some microscopic information (e.g. force-chain, averaged pure rotation rate and bond distributions).